The lion & the mouse - Pinkney, Jerry; Aesop (New York : Little, Brown and Co. Books for Young Readers, 2009)
In this wordless retelling of an Aesop fable, an adventuresome mouse proves that even small creatures are capable of great deeds when he rescues the King of the Jungle.
Booklist starred
Caldecott Medal/Honor
School Library Journal starred
Booklist starred, July 2009
Bulletin (Center for Children's books), November 2009
Horn Book Starred, November 2009
Keywords: Fables; Folklore; Fables; Folklore; Stories without words; Fables; Folklore; Stories without words; Picture books for children